Measuring the Impact of Influencer Campaigns on Customer Retention for Major Brands - Miftah, Andi (Journal of Social Commerce, 2023)
The present research aims at establishing the effect of credibility of influencers and the quality of the content shared on customer loyalty to the large brands. Employing a quantitative research approach, the data were obtained from Personal Influence Communication participants involved in influencer campaigns from different sectors. The findings shows that the influencer factors such as credibility which involves trustworthiness, expertise, and attractiveness have direct and positive relation with customer retention and the content factors like relevancy, engagement, and information content predict customer retention. For most of these factors, correlation and regression analyses reveal positive associations with retention figures and results that are generally slightly stronger for content quality. Also, the result shows the significance of the difference in retention rates between the industry sectors and the validity of these predictors across demographic categories. These data suggest that people see credible influencers as well as quality content as the key to maintaining and constantly building customer engagement, making it possible to draw pertinent conclusions on the most optimal way to approach influencer marketing.